Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 4 - Section 4.3 - Integrated Review - Summary on Solving Systems of Equations: 1

Answer

(2, 5)

Work Step by Step

Use the substitution method to insert the equation for y into the first equation: 2x - 3(4x - 3) = -11 Solve for x: 2x - 12x + 9 = -11 -10x + 9 = -11 -10x = -20 x = 2 Let x = 2 in the second equation to find y: y = 4(2) - 3 = 5 Check the solution (2, 5) in the first equation: 2(2) - 3(5) = -11 4 - 15 = -11 -11 = -11; True
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.